1994
DOI: 10.1007/bf00231963
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of in vitro-grown apical meristems of wasabi (Wasabia japonica) by vitrification and subsequent high plant regeneration

Abstract: In vitro-grown apical meristems of wasabi (Wasabia japonica Matsumura) were successfully cryopreserved by vitrification. Excised apical meristems precultured on solidified M S medium containing 0.3M sucrose at 20°C for 1 day were loaded with a mixture of 2M glycerol and 0.4M sucrose for 20 min at 25°C. Cryoprotected meristems were then sufficiently dehydrated with a highly concentrated vitrification solution (designated PVS2) for 10 min at 25°C prior to a plunge into liquid nitrogen. After rapid warming, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 11 publications
6
101
0
5
Order By: Relevance
“…Preculturing shoot tips on solidified medium with a high sucrose concentration is extremely effective at inducing osmo-tolerance for cryopreservation in many plant species (Engelmann et al 2008;Sakai et al 2008). Similarly, LS treatment is very effective at improving the regrowth rate after cryopreservation and is used for many plant species (Matsumoto et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Preculturing shoot tips on solidified medium with a high sucrose concentration is extremely effective at inducing osmo-tolerance for cryopreservation in many plant species (Engelmann et al 2008;Sakai et al 2008). Similarly, LS treatment is very effective at improving the regrowth rate after cryopreservation and is used for many plant species (Matsumoto et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Osmoprotection regulates the osmotic dehydration of tissues which increases the growth recovery (Matsumoto et al, 1994). Through osmosis, cryoprotectant replaces vacant spaces available in cells when free moving water particles left the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Panis et al (2005b) showed that regrowth of banana meristems is not influenced by loading solution exposure time (0 -5 hours). Although the precise mechanism of loading is not yet fully understood, it has been proven for different plant species that loading can dramatically enhance the tolerance of isolated meristems to dehydration by the vitrification solution (Matsumoto et al 1994, Takagi et al 1997, Panis 2009.…”
Section: IImentioning
confidence: 99%